A Restriction on Recursion. (20th January 2018) - den Dikken, Marcel; Dékány, Éva
Abstract: Universal Grammar places a restriction on self‐embedding recursion structures created through External Merge: A phasal category of type α can be embedded in a phasal category of the same type where there is a c‐command relation between the heads of the two instances of α only if the two instances of α are separated by a phase head. This restriction (the exact counterpart of the familiar c‐command cum phasemate requirement that is imposed on identical copies of a single category under Internal Merge) explains a variety of hitherto poorly understood properties of the noun phrase. The set of elements that are eligible to serve as nondative possessors in Hungarian possessive DPs is shown to fall out from the recursion restriction: all and only those possessors that are not as large as DP can be placed in the caseless possessor position in the immediate c‐command domain of the D head of the possessive noun phrase; dative possessors are in the specifier position of the possessive DP, not c‐commanded by its D head and hence immune to the recursion restriction. The recursion restriction sheds new light on the syntax of the possessive noun phrase, the nature of possessor drop, and the structure and distribution of demonstratives. The analysis also presents an empirical case for labeling of XP–YP structures via ϕ‐feature sharing.